THE NEED FOR VIRTUAL ETHICS IN DAN BROWN'S DIGITAL FORTRESS: SOCIOLOGICAL APPROACH - INDRIAWATI, IKA NOFI (2009)
The research is proposed to analyze the need for virtual ethics in a novel with the title Digital Fortress with Sociological Approach. There are two objectives: the first is to analyze the novel in term of structural elements, and the second is to analyze the novel based on Sociological Approach. This study is a descriptive qualitative study, using the novel of Dan brown's Digital fortress as the object of analysis. There are two kinds of data sources use in the analyzing, namely primary and secondary data sources. The primary data are the novel itself and the secondary data sources are books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. In this study, the writer draws some conclusion as follows. First, based on the structural analysis, it is evident that in Digital Fortress, Dan Brown wants to deliver a message that virtual ethics is necessary to guarantee the civil rights of privacy. Secondly, based on the sociological analysis it shows the social condition of American society in late twentieth century. It portrays the need for virtual ethics in order that the citizens get safety on their privacy area.